A noise-robust damage indicator for characterizing singularity of mode shapes for incipient delamination identification in CFRP laminates. (15th April 2019) - Xu, Wei; Fang, Hongyuan; Cao, Maosen; Zhou, Limin; Wang, Quan; Ostachowicz, Wiesław
Highlights: 2D modal Teager-Kaiser energy can reveal singularity of mode shapes. Noise robustness is enhanced in 2D multi-resolution modal Teager-Kaiser energy. A noise-robust damage indicator is formulated for damage identification. The damage indicator is experimentally validated by non-contact laser measurement. Abstract: Identification of delaminations in the early stage is crucial to ensure the safety of CFRP laminates. In the modal domain, high spatial sampling resolution of a mode shape is required for precise location of incipient delamination. Non-contact measurement relying on laser scanning technology allows measured mode shapes to be densely sampled. Unfortunately, noise components usually contaminate such densely-sampled mode shapes, easily causing intense noise interference that likely masks actual delamination features. To address this issue, a noise-robust damage indicator is formulated for designating the presence and location of incipient delamination in CFRP laminates under noisy environments. This damage indicator is created by introducing a 2D multi-resolution modal Teager-Kaiser energy for characterizing delamination-caused singularity of mode shapes. Proof of concept of the damage indicator is numerically undertaken in finite-element CFRP laminates with incipient delaminations, with emphasis on sensitivity to damage as well as robustness against noise. The applicability of the damage indicator is experimentally validated on a CFRP laminate with an incipient delamination, mode shapes of which are precisely acquired via the non-contact measurement using a scanning laser vibrometer. The numerical and experimental results show that the damage indicator can effectively identify the presence and location of incipient delamination in CFRP laminates under noisy environments.